Acute Suppurative Thyroiditis Secondary to Tuberculosis with Superimposed Bacterial Infection: A Case Report - Wan Azman, Siti Sanaa binti; Mohamad, Masni binti (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Acute suppurative thyroiditis is a rare and potentially fatal condition. We present a case of an 18-year-old Malay female who presented with one-week history of painful right sided neck swelling, fever and odynophagia. Neck CT confirms ruptured multiloculated abscess with posterosuperior extension into prevertebral space. Pus and tissue cultured Streptococcus anginosus and Eikenella corrodens with positive TB PCR. She responded well to ampicillin/ sulbactam and anti-tuberculosis treatment with no evidence of residual collection from ultrasound.